Genomic analysis of a multidrug methicillin-resistant staphylococcus epidermidis recovered from the urine of a guinea pig (Cavia porcellus) with suspected pyelonephritis - Gaeta, Natália C.; Hellmeister, Alexandre; Possebon, Fábio S. [UNESP]; Araujo, João P. [UNESP]; Heinemann, Marcos B. (Springer Nature, 2023)
Staphylococcus epidermidis is an emerging pathogen causing infant pyelonephritis. There is a lack of genomic data on Staphylococcus epidermidis as the etiology of pyelonephritis and its resistant determinants. In this study, we have conducted a genomic and microbiologic investigation of an S. epidermidis recovered from the urine of a guinea pig with suspected pyelonephritis in Brazil. The genome was sequenced using the Illumina MiSeq platform and de novo assembled using SPades. Resistome, virulome, and plasmidome were in silico predicted using bioinformatics tools. Data analysis revealed that S. epidermidis USP-LZB-G06 belonged to sequence type ST332. Strikingly, a broad resistome (antibiotics, hazardous heavy metals, and biocides) was predicted, including the presence of the clinically relevant mecA, blaZ, and qacA efflux pump genes. SNP-based analysis revealed that strain USP-LZB-G06 was clustered along mecA positive S. epidermidis strains of ST332 isolated between 2008 and 2016 from humans in Australia and the United States of America. Our results indicate that the detection of this microorganism should be considered as a urinary tract infection agent in exotic pets, particularly guinea pigs. In addition, there is an urgent need to update veterinarians regarding the detection and therapeutic management of these microorganisms.
Keywords: Antimicrobial resistance; blaZ; Critical pathogens; Genomic surveillance; mecA; One health